Helpers "Here on the Front Lines": Welfare‐to‐Work Managers' Moral Identity Work. Issue 1 (15th August 2017) - Taylor, Tiffany; Turgeon, Brianna; Gross, Christi L.
Abstract : Using data drawn from telephone interviews with Ohio Works First program managers ( N = 69), we examine managers' moral identity work. This work included using militarized rhetoric to evoke moral identities as honorable workers. It also involved signifying helper/helpful moral identities by defining what it means to be helpful, legitimating their helper identity through connections to caseworkers, and affirming their identity through telling success stories. Additionally, managers implicitly othered clients they viewed as needy and politicians they considered to be out‐of‐touch. Our research contributes to the literature on welfare‐to‐work, but also more broadly to our understanding of moral identity work and implicit othering.